Molecular markers as a method to evaluate the movement of Hypothenemus hampei (Ferrari). Issue 1 (13th June 2015) - Gil, Zulma Nancy; Benavides, Pablo; Souza, Og De; Acevedo, Flor Edith; Lima, Eraldo
Abstract : The objective of this research was to develop a methodology to describe the movement of the coffee berry borer Hypothenemus hampei (Coleoptera: Curculionidae) in the field through: (i) the evaluation of allele variation of a microsatellite marker on polymorphic Colombian H. hampei populations; (ii) the invention of a device for releasing H. hampei adults; (iii) the standardization of a release-recapture technique for H. hampei populations; (iv) the estimation of the flight distance of the insect; and (v) the calculation of a mathematical expression that describes the movement of H. hampei in space over time. The results indicated that: (i) the microsatellite molecular marker HHK.1.6 was exclusively present in a population from Guapotá-Santander, was dominant and allows the evaluation of H. hampei movement for several generations; (ii) a device that released 88.8% of H. hampei adults in 2 s was designed; (iii) this device was used as H. hampei populations containing HHK.1.6 marker release strategy, and coffee seeds as recapture strategy; (iv) it was estimated that H. hampei adults flew as far as 65 m, however, 90% were recovered in a radius of <40 m. Finally, (v) the mathematical expression that described the movement of H. hampei in space over time was Y ^ = α β X i, being Y ^ the average number of borer beetles recaptured per tree, and x the distance in meters. This method will allow to determine the movement of H. hampei from different environmental and ecological scenarios.